Perbandingan Penawaran Investasi Depostio Bank Syariah - Hery Harjono Muljo; Holly D (Bina Nusantara University, 2010)
From the beginning, the sharia banks operation is always supporting mosleem expectations. Economic recovery, fairness, security, and comfortness aspects are became ultimate goals of sharia bank in Indonesia. This research is comparing the investment deposits from 3 sharia banks, and 4 business units of sharia, by using comparative descriptive analysis. The comparative variables were devided into 3 categories; there are Nisbah (profit sharing), investment conditions, and bank fascilities. The results indicates that BNI has the highest nisbah between all sharia banks at the first category. Bank Muamalat Indonesia, BNI Sharia, Bank Sharia Mega Indonesia has the lowest openning balance of time-deposits at second category . The product fascility as the third category, indicates that Bank Sharia Mandiri, BNI Sharia, Bank Sharia Mega Indonesia, and Bank Muamalat can using multi currency. BTN Sharia, Bank Sharia Mega Indonesia, Bank Muamalat Indonesia, and Bank Danamon Sharia were also offer joint account in their sharia investment.